Novel isatin conjugates endowed with analgesic and anti-inflammatory properties: design, synthesis and biological evaluation - Brown L.D.; Girgis A.S.; Patel S.; Samir N.; Said M.F.; Baidya A.T.K.; Kumar R.; Moore J.; Khadanga A.; Sakhuja R.; Panda S.S. (My University, 2025)
Aims: This study aimed to develop novel molecular hybrid conjugates integrating isatin, rhodanine, and phthalimide pharmacophores to create effective analgesic and anti-inflammatory agents with improved safety profiles over existing treatments. Materials & Methods: A series of hybrid conjugates (4a–l) were synthesized and evaluated through in vitro and in vivo biological assays. The most promising compound, 4c, underwent extensive pharmacological and toxicological evaluations. Molecular docking, molecular dynamics simulations, and 2D-QSAR studies were performed to elucidate the mechanism of action and validate the experimental findings. Results: Compound 4c exhibited potent analgesic and anti-inflammatory activity, effectively inhibiting COX-2 and pro-inflammatory cytokines (IL-6 and TNF-α). Its superior selectivity index (SI) was 1.11 compared to 0.67 for indomethacin. It demonstrated an ulcer index of 2.9 versus 10.23 for indomethacin, indicating reduced gastrointestinal toxicity. Molecular docking simulations revealed a strong binding affinity with COX-2 (−9.832 kcal/mol), and molecular dynamics confirmed the stability of the COX-2 complex. Conclusions: Compound 4c emerged as a promising lead candidate for developing safer and more effective anti-inflammatory and analgesic agents. Its robust efficacy, safety profile, and computational validation highlight its potential for further optimization in therapeutic applications. © 2024 Informa UK Limited, trading as Taylor & Francis Group.